Validation of the yale‐brown obsessive compulsive scale modified for binge eating. Issue 7 (1st June 2015) - Deal, Linda S.; Wirth, R.J.; Gasior, Maria; Herman, Barry K.; McElroy, Susan L.
ABSTRACT Objective Establish the Yale–Brown obsessive compulsive scale modified for binge eating (YBOCS‐BE) as a fit for purpose measure of treatment benefit in clinical trials of binge eating disorder (BED). Methods YBOCS‐BE psychometric properties were evaluated with data from a Phase 2 randomized controlled trial of lisdexamfetamine dimesylate in 260 adults with BED. Assessments included: Cohen's effect size estimates of item‐level sensitivity and scale‐level external responsiveness; item‐to‐total correlations; Cronbach's alpha for internal consistency reliability; Spearman correlations against reference measures for construct validity; known‐groups analyses for discriminating ability; t tests of within‐group differences between baseline and post baseline visits for internal responsiveness; and multiple anchor‐based approaches to estimate minimum clinically important change (MCIC). Results No significant distribution anomalies were seen. Items appear sensitive to treatment group differences. Item‐to‐total correlations were positive. Internal consistency is 0.81. Large correlations (>0.50) were seen between YBOCS‐BE score change and the Clinical Global Impression–Improvement (CGI‐I; 0.58) and score changes for the following; number of binge days (0.38), Clinical Global Impression–Severity (CGI‐S; 0.57), the disinhibition (0.57) and hunger (0.52) subscales of the Three‐Factor Eating Questionnaire (TFEQ), and the Barratt Impulsiveness Scale (BIS‐11; 0.58). MCIC estimates range from −4 to −17. Discussion The YBOCS‐BE was found to be a reliable and valid measure of an important and unique concept in BED‐related clinical studies. Study limitations include using protocol‐defined BED severity level and the exclusion of psychiatric comorbidities. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:994–1004).